Trade costs and global value chain positioning in China’s manufacturing industry: A systematic literature review - Zhou, Li; Zaidi, Mohd Azlan Shah; Mansur, Mustazar (Edelweiss Applied Science and Technology, 2025)
Countries’ positioning within global value chains (GVCs) has become critical for determining trade margins and economic influence, with trade costs emerging as a crucial determinant beyond traditional factor endowments and economies of scale. Under the combined influence of the evolution of the international division of labor, trade protectionism, and the COVID-19 pandemic, GVCs have entered a restructuring stage, which presents new trade cost challenges. This systematic literature review examines how trade costs affect China’s manufacturing GVC positioning through the analysis of 49 high-quality articles selected from 1,072 initial papers retrieved from Web of Science (1999-2023). The review addresses three fundamental questions: factors affecting China’s trade costs along with their measurement methods, trade cost differences across GVC stages, and impact mechanisms on China’s manufacturing positioning. The analysis tackles critical methodological challenges, including double-counting problems in traditional trade statistics and transmission mechanisms whereby upstream trade barriers magnify downstream costs. This review provides comprehensive insights into how trade costs influence GVC production divisions, offering theoretical foundations for policy interventions aimed at industrial upgrading.